Manage Cloud Data Access Control Anonymity with Attributed Based Encryption - Prashanth, Thirumanapally; Rao, Gundu Purna Chandar (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a revolutionary computing paradigm, which enables flexible, on-demand, and low-cost usage of computing resources, but the data is outsourced to some cloud servers, and various privacy concerns emerge from it. Various schemes based on the attribute-based encryption have been to secure the cloud storage. Data content privacy. A semi anonymous privilege control scheme AnonyControl to address not only the data privacy. But also the user identity privacy. AnonyControl decentralizes the central authority to limit the identity leakage and thus achieves semi anonymity. The Anonymity –F which fully prevent the identity leakage and achieve the full anonymity.